PERANAN ASOSIASI PENGACARA SYARI’AH INDONESIA (APSI) DALAM UPAYA PENYELAMATAN ASET KREDITUR MELALUI FIDUSIA - Achmad Nur Qodin (Jurnal Penelitian, 2014)
THE ROLE OF ISLAMIC INDONESIAN LAWYERS ASSOCIATION IN RESCUING CREDITORS ASSET THROUGH FIDUCIARY. One type of collateral material that is often used by the BMT Fastabiq is fiduciary. Collateral objects pledged by the debtor to the bank are such as vehicles and machinery equipment. They are burdened fiduciary and apparently damaged, destroyed, and the value of  the moving objects will shrink every year. This study intended to study the role of  the role of  Islamic Indonesian lawyers association  (APSI)  in  rescuing  creditors  assests  through  fiduciary at KJKS BMT Fastabiq Pati and APSI efforts in conducting legal protection toward creditors on the collateral objects destruction in KJKS BMT Fastabiq Pati. Model of this research was a socio-juridical study. That was based on a legal provision (regulations) with the phenomenon or the fact that occur in the field as well as in practice, according to what happened and the truth. The results showed that APSI has an important role in rescuing the creditors assets through fiduciary at BMT KJKS Fastabiq Pati. In rescuing the assets, APSI made several attempts, namely: 1). Preventive measures. 2). Fiduciary Registration. 3. Repressive efforts. According to UU No. 42 of  1999, debtors are still responsible to repay their loans even after they fiduciary loans are insured or not insured.Keywords: ‘Shari’ah’ Lawyers, Creditors, Debtors, FiduciarySalah satu jenis jaminan kebendaan yang sering dipakai oleh pihak BMT Fastabiq adalah jaminan Fidusia. Benda jaminan yang dijaminkan oleh pihak debitur kepada pihak bank terutama pada benda jaminan seperti kendaraan bermotor, peralatan mesin  yang dibebani jaminan Fidusia ternyata rusak, musnah, dan nilai dari benda bergerak tersebut setiap tahun akan menyusut. Penelitian ini bermaksud mengkaji peranan  APSI  dalam  upaya  penyelamatan asset kreditur melalui Fidusia di KJKS BMT Fastabiq Pati, serta upaya APSI dalam melakukan perlindungan hukum terhadap kreditur atas musnahnya benda jaminan Fidusia di KJKS BMT Fastabiq Pati. Model penelitian ini adalah penelitian yuridis-sosiologis yaitu  suatu  penelitian  yang  didasarkan  pada  suatu  ketentuan hukum (peraturan yang berlaku) dengan fenomena atau kenyataan yang  terjadi  di  lapangan  serta  dalam  prakteknya  sesuai  dengan yang terjadi dan sebenarnya. Hasil penelitian menunjukkan bahwa APSI mempunyai peranan penting dalam upaya penyelamatan asset kreditur  melalui  Fidusia  di KJKS BMT Fastabiq Pati. Dalam penyelamatan asset tersebut, APSI melakukan beberapa upaya, yaitu: 1). Upaya preventif. 2). Pendaftaran Jaminan Fidusia. 3. Upaya represif. Menurut Undang-Undang Nomor 42 Tahun 1999 adalah debitur tetap bertanggungjawab mengembalikan pinjaman kredit walaupun benda jaminan Fidusia tersebut diasuransikan maupun tidak diasuransikan.Kata kunci: Pengacara Syari’ah, Kreditur, Debitur, Fidusia